Exploring the influence of differentiated nutrition information on consumers’ mental models regarding foods from edible insects: A means-end chain analysis - Pambo, K.O.; Okello, J.J.; Mbeche, R.M.; Kinyuru, J.N. (Informa UK Limited, 2017)
This study used a field experiment and means-end chain analysis to examine the effects of positive and perceived negative nutrition information on the households’ motivations to consume insect-based foods. It used a random sample of households drawn from rural communities in Kenya. The study found that provision of nutrition information on benefits of edible insects and perceived negative aspects of insect-based foods influences participants’ perceptions of insect-based foods and hence acceptance. We also found that tasting real products influenced the nature of mental constructs. The results provide marketers of edible insects with potential marketing messages for promotion.